Of neurons and pericytes: The neuro-vascular approach to diabetic retinopathy. (2020) - Eleftheriou, Cyril G.; Ivanova, Elena; Sagdullaev, Botir T.
Abstract: Diabetic retinopathy (DR) is a frequent complication of diabetes mellitus and an increasingly common cause of visual impairment. Blood vessel damage occurs as the disease progresses, leading to ischemia, neovascularization, blood–retina barrier (BRB) failure and eventual blindness. Although detection and treatment strategies have improved considerably over the past years, there is room for a better understanding of the pathophysiology of the diabetic retina. Indeed, it has been increasingly realized that DR is in fact a disease of the retina's neurovascular unit (NVU), the multi-cellular framework underlying functional hyperemia, coupling neuronal computations to blood flow. The accumulating evidence reveals that both neurochemical (synapses) and electrical (gap junctions) means of communications between retinal cells are affected at the onset of hyperglycemia, warranting a global assessment of cellular interactions and their role in DR. This is further supported by the recent data showing down-regulation of connexin 43 gap junctions along the vascular relay from capillary to feeding arteriole as one of the earliest indicators of experimental DR, with rippling consequences to the anatomical and physiological integrity of the retina. Here, recent advancements in our knowledge of mechanisms controlling the retinal neurovascular unit will be assessed, along with their implications for future treatment and diagnosis of DR.